Hydrogen bond‐Driven Self–Assembly between Amidinium Cations and Carboxylate Anions: A Combined Molecular Dynamics, NMR Spectroscopy, and Single Crystal X‐ray Diffraction Study. Issue 13 (23rd May 2017) - Thomas, Michael; Anglim Lagones, Thomas; Judd, Martyna; Morshedi, Mahbod; O'Mara, Megan L.; White, Nicholas G.
Abstract: A combination of molecular dynamics (MD), NMR spectroscopy, and single crystal X‐ray diffraction (SCXRD) techniques was used to probe the self–assembly of para ‐ and meta ‐bis(amidinium) compounds with para ‐, meta ‐, and ortho ‐dicarboxylates. Good concordance was observed between the MD and experimental results. In DMSO solution, the systems form several rapidly exchanging assemblies, in part because a range of hydrogen bonding interactions is possible between the amidinium and carboxylate moieties. Upon crystallization, the majority of the systems form 1D supramolecular polymers, which are held together by short N−H⋅⋅⋅ O hydrogen bonds. Abstract : Understanding self–assembly : The interaction between bis(amidinium) cations and dicarboxylate anions was studied in a range of solvents using NMR spectroscopy and molecular dynamics techniques. The results indicate that both linear and cyclic architectures are present in solution, and they can be crystallized to give 1D hydrogen bonded polymeric systems.